MeV irradiation of tungsten nanowires: structural modifications - Grossi, Joás Santiago (2020)
In this work we use the Two Temperature Model coupled to Molecular Dynamics (TTM-MD) to study swift heavy ion irradiation of W finite nanowires. Au projectiles are considered with energies ranging from 20 to 50 MeV, which correspond to electronic stopping values less than 20 keV nm-1 in the regime where electronic stopping is larger than nuclear stopping. Nanowires with diameters much smaller than the electron mean free path are considered for two different sizes with an aspect ratio ∼3.7 between length and diameter. Nanowires display radiation-induced surface roughening, sputtering yields and the formation of point defects and di-vacancies. For the smallest size, a hole stays opened in the central part of the wire for S e > 12.6 keV nm-1. W nanofoams, considered as collections of connected nanowires like those simulated here, are expected to behave similarly under irradiation displaying radiation resistance for the electronic stopping range that has been considered. In fact, nanowires larger than tens of nm would be needed for defect accumulation and lack of radiation resistance.